Suboptimal Automatic Generation Control of Conventional Power Systems - Ram Naresh Mishra (International Journal of Advanced Science and Technology, 2020)
This article presents suboptimal automatic generation control of thermal-thermal (nonreheat) and hydrothermal energy systems when they are subjected to load disturbance of 1%. For these systems, the interconnection is considered as the HVDC link for thermal-thermal system while the interconnection such as the EHVAC link in parallel with the HVDC link is consideredfor hydrothermal system. The dynamic model of the incremental power flow across the HVDC link is based solely on the frequency difference at the end of the rectifier. The HVDC link is considered to operate in constant current control mode. To carry out the research, suboptimal controllers for AGC are designed using a more comprehensive proportional-integral control strategy. System responses are simulated using Matlab. In addition, to study the stability of the closed loop systems, the eigenvalues ​​are determined.